Caracterización del gasto según las Normas Internacionales Autorizadas en materia de Auditoría del Sector Público (ISSAI) en la empresa de servicios las Ceibas E.S.P de Neiva (Huila) año 2020 (2022)
The present investigation is characterized in determining the management of public sp ending in the public utility company Las Ceibas E.S.P according to Authorized International Standards on Public Sector Auditing (ISSAI). According to the expense report (internal control), La Ceibas company presents a significant increase in expenses gener ated in maintenance, publicity and propaganda, restaurant expenses, fines and penalties. The Municipal Comptroller's Office in the process of financial and management audit in the evaluation of the macro process of budget management that includes the execu tion of the expense indicates that a significant budget deficit of 22 billion pesos is reflected. The methodological approach is mixed, type IV: Exploratory research, with qualitative data and statistical analysis. The scope of research is determined by co mbining the types of exploratory and descriptive studies. The research design is a sequential explanatory design with elements of the sequential exploratory design. A semistructured survey is carried out. The research phases are implemented to fulfill the central objective of the project. It was possible to establish that there is an overestimation in the amount of the value of the expenses and this makes the situation of sustainability and stability complicated. In conclusion, the behavior is unbalanced i n the execution of the budget of income and expenses of the entity during the 2020 term and this is due to the fact that the activities are not aimed at complying with any of the mission objectives of the entity.